Strategi Inovasi Dalam Manajemen Bisnis Syariah: Studi Kasus UMKM di Indonesia - Rahmat, Alvin; Susilawati, Sumita; Hasanah, Uswatun (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze innovation strategies in sharia business management in the SME sector in Indonesia. The research method used is qualitative with a case study approach in several sharia-based SMEs. Data was collected through in-depth interviews, observation, and documentation. The research results show that the innovation strategies implemented include product innovation, process innovation, and marketing innovation based on sharia principles such as product halalness, transaction fairness, and information transparency. Constraints faced in implementing innovation include limited human resources, technology, and understanding of sharia concepts. This study concludes that innovation based on sharia values is the key to the sustainability of sharia SMEs amid modern market competition.